Interrelationships among dry season leaf fall, leaf flush and transpiration: insights from sap flux measurements in a tropical dry deciduous forest. Issue 3 (1st July 2015) - Iida, Shin'ichi; Shimizu, Takanori; Tamai, Koji; Kabeya, Naoki; Shimizu, Akira; Ito, Eriko; Ohnuki, Yasuhiro; Chann, Sophal; Keth, Nang
Abstract: We measured the sap flux densities of 12 deciduous trees in a tropical dry deciduous forest with high seasonality of available water located in Cambodia and evaluated the seasonal trends in transpiration and leaf phenology. For all trees, the minimum transpiration was recorded in the middle of the dry season, and almost all trees restarted transpiration before the first monsoon rain. The occurrence of the 'paradox' of leaf phenology was confirmed. During the dry season, transpiration was controlled by leaf phenology and decreased with an increase in the duration of the leafless period. In contrast, during the wet season, daily changes in transpiration were determined by changes in evaporative demand. Transpiration during the dry season accounted for more than 30% of the annual total among trees, and at the stand scale, the dry season contribution was 38%. The dry season transpiration was not negligible for the water balance in this ecosystem. The soil water condition in the shallow layer, where the main root system is located, was not the source of transpiration during the dry season. This implied that the root probably extended to a deep layer and absorbed water. The relationships between the mean canopy stomatal conductance and vapour pressure deficit revealed that most trees were isohydric. Isohydric behaviour controlling stomatal openness to avoid xylem hydraulic failure was also confirmed at the stand scale and was advantageous for these trees, allowing them to continue transpiring under the high evaporative demand during the dry season. Copyright © 2015 John Wiley & Sons, Ltd.